Heart transplantation in children with intellectual disability: An analysis of the UNOS database. (9th December 2016) - Goel, Alexander N.; Iyengar, Amit; Schowengerdt, Kenneth; Fiore, Andrew C.; Huddleston, Charles B.
Abstract: Heart transplantation in children with intellectual disability (ID) is an issue of debate due to the shortage of available donor organs. We sought to perform the first large‐scale retrospective cohort study describing the prevalence and outcomes of heart transplantation in this population. The United Network of Organ Sharing database was queried from 2008 to 2015 for pediatric patients (age <19 years) receiving first, isolated heart transplant. Recipients were divided into three subgroups: definite ID, probable ID, and no ID. The chi‐square test was used to compare patients' baseline characteristics. Kaplan‐Meier and Cox proportional hazard regression analyses were used to estimate the association between ID and death‐censored graft failure and patient survival. Over the study period, 565 pediatric patients with definite (131) or probable (434) ID received first heart transplant, accounting for 22.4% of all first pediatric heart transplants (n=2524). Recipients with definite ID did not significantly differ from those without ID in terms of gender, ethnicity, ischemia time, severity of pretransplant condition (waitlist status, mechanical ventilation, inotrope dependence, ECMO, VAD, PVRI, infection prior to transplant), or incidents of acute rejection within the first year. ID was associated with prolonged waitlist time ( P <.001). Graft and patient survival at 3 years was equivalent between children with and without ID ( P =.811 and .578, respectively). We conclude that intellectual disability is prevalent in children receiving heart transplants, with 22.4% of recipients over the study period having definite or probable ID. ID does not appear to negatively affect transplantation outcomes. Future studies are needed to assess long‐term outcomes of transplantation in this population.